2012
DOI: 10.1016/j.juro.2011.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Lower Prevalence of Varicoceles in Obese Patients Found on Routine Scrotal Ultrasound

Abstract: Obese patients have a lower prevalence of varicoceles detected by ultrasound. The lower prevalence is independent of physical examination and more likely due to another factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 12 publications
0
30
1
Order By: Relevance
“…However, a recent study showed that obese patients had a lower prevalence of varicocoele than normal weight men after detection by ultrasound or physical examination. Therefore, the authors concluded that the difference in prevalence was not because of difficulties with the physical examination caused by obesity (Chanc Walters et al, 2012). In summary, the inverse association between varicocoele and BMI is because of a decreased nutcracker effect in men with a higher BMI.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, a recent study showed that obese patients had a lower prevalence of varicocoele than normal weight men after detection by ultrasound or physical examination. Therefore, the authors concluded that the difference in prevalence was not because of difficulties with the physical examination caused by obesity (Chanc Walters et al, 2012). In summary, the inverse association between varicocoele and BMI is because of a decreased nutcracker effect in men with a higher BMI.…”
Section: Discussionmentioning
confidence: 95%
“…With regard to a possible explanation for the inverse association between varicocoele and BMI, many researchers suggested that increased amounts of adipose tissue may decrease compression of the left renal vein and provide a cushion, decreasing the nutcracker effect in men with a higher BMI (Handel et al, 2006;Nielsen et al, 2006;Tsao et al, 2009). Therefore, the authors concluded that the difference in prevalence was not because of difficulties with the physical examination caused by obesity (Chanc Walters et al, 2012). However, a recent study showed that obese patients had a lower prevalence of varicocoele than normal weight men after detection by ultrasound or physical examination.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation of the association is the reduced detection rate of varicocele in men with excess bodyweight because of the difficult palpation in general physical examination for the existence of adipose tissue in the groin and scrotum (Coolsaet, 1980;Handel et al, 2006). While a research conducted by Chanc Walters et al (2012) suggested that men with excess bodyweight had a lower incidence of varicocele than men with normal weight after detection by physical examination or ultrasound, they came to the conclusion that the diversity in prevalence was not because of the presence of difficulties in the physical examination for a higher BMI. In general, the correlation between varicocele and BMI is due to a reduced nut- (Das, Prasad, Szmigielski, & Noorani, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…After these analyses, six studies were removed and there were 13 articles containing seven case-control studies (Chanc Walters, Marguet, & Crain, 2012;Chen & Huang, 2010;Gorur et al, 2015;Handel, Shetty, & Sigman, 2006;Kılıç et al, 2007;Liu et al, 2015;Shafi & Agajani, 2015) and six observational crosssectional studies (Gokce, Demirtas, Ozturk, Sahin, & Ekmekcioglu, 2013;Liu et al, 2017;Rais et al, 2013;Söylemez, Atar, Sancaktutar, Bozkurt, & Penbegül, 2011;Tsao et al, 2009;Yigitler, Yanardag, Silit, & Alpay, 2012) remained. Among these relevant investigations, 144 different articles were obtained without duplication.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…A recent study showed that microsurgical varicocele ligation resulted in a significant increase in serum testosterone levels in more than two-thirds of men (14). In addition, some studies have shown that BMI has a protective effect for the development of varicocele (33,34). However, there seems to be an inverse relation between BMI and serum levels of testosterone, and varicocele could be involved in this relationship.…”
Section: Discussionmentioning
confidence: 99%